An Exploratory Study of Telomere Length in the Deep-Sea Shark, Etmopterus granulosus - Nehmens, Melissa C.; Varney, Rebecca M.; Janosik, Alexis M.; Ebert, David A. (Frontiers in Marine Science, 2021)
The history of elasmobranch ageing highlights the difficulty of age estimation in animals lacking ossified structures. Ageing techniques are limited due to difficulties in validation and verification of ageing estimates. Additionally, sample scarcity hinders progress due to hesitation of risking a limited number of samples on exploratory techniques. This study explored the use of genetic analysis of telomeres as a method of age determination. Telomeres were amplified with qPCR, compared across samples, and were found to differ significantly across size classes. More work is needed to determine whether telomeres consistently correlate with size class across elasmobranchs. However, telomeres offer easily obtained data that can be combined with current methods to provide additional points of comparison for elasmobranch biology. Our results underscore the importance of expanding current ageing methods and highlight a necessary distinction between chronological and biological ages when describing elasmobranch populations.